(untitled) (The International Research Journal of Management Science, 2021)
This study aims to investigate the important academic factors; teaching method, study habits of students and attendance of students that affect students’ academic performance. The study used a survey method and analytical research design. A stratified sampling method was used to select 150 respondents from 1,525 total number of undergraduate students from four high student enrolment community colleges of Bhaktapur district. Regression analysis was used to identify the impact of independent variables on student’s academic performance. Mann-Whitney test was used to identify the differences between perceived student’s performance across gender, age and faculty. To test for differences between perceived student’s performance across study year and guardian occupation, Kruskal-Wallis test was conducted. The result shows that the teaching method and attendance of students have a significant positive impact on perceived student’s performance but student’s habit has no significant impact on perceived student’s performance. However, it has been proved that gender, age, faculty, study year and guardian occupation do not have any differences in perceived student’s performance.